A Review on Epidermal Nanogenerators: Recent Progress of the Future Self‐Powered Skins. Issue 8 (22nd May 2022) - Nguyen, John Tan; Cheng, Wenlong
Abstract : Epidermal nanogenerators (ENGs), defined as nano‐enabled, thin, soft, and flexible skin‐like devices that can convert mechanical and thermal energy into electricity, are emerging as a promising self‐powered technology for wearable biomedical devices. This review covers the discussion of working mechanisms, design strategy, and major requirements of the state‐of‐the‐art ENGs including piezoelectric, triboelectric, pyroelectric, and hybrid. In addition, their representative applications in human–machine interface (HMI), wound healing, and wearable biomedical sensors are described. In particular, a focus has been on the narration of self‐powered ENG‐based biosensors for detecting physical, biochemical, and physiological signals. Despite the encouraging advances over the past decade, the field of ENGs remains in the early stage of development with limited real‐world adoption. There remain a number of challenges such as insufficient energy and power density for powering wearable devices, poor air permeability, limited washability, and durability under severe conditions. The future opportunity lies at the development of better materials and/or designs to tackle these challenges to generate real‐world impact. Abstract : This article reviews the recent development in the burgeoning field of epidermal nanogenerators, which may render it possible to realize next‐generation self‐powered, soft wearable diagnostics anytime anywhere. The review covers the discussions of the working principles, design parameters, and novel applications in human–machine interface (HMI), self‐healing, wound healing, and self‐powered biosensors.